Wisdom-of-the-crowd effect's application in environmental impact assessment. Issue 1 (11th September 2019) - Oguzcan, Semih; Tugnoli, Alessandro; Dvarioniene, Jolanta
Abstract : The wisdom-of-the-crowd effect is a counter-intuitive phenomenon that results in the reduction of errors under some strict conditions. Those conditions are related to randomness and large enough sample size. Many research fields examine the potential use of this effect in error reduction and in overcoming limitations such as the limited number of experts in a given field. Selected environmental/human health impact assessments have been qualitatively examined for the potential existence of this phenomenon. In addition, a quantitative evaluation has been performed for four case studies of simplified life-cycle assessment. The quantitative results indicate that for end-point damage categories, the geometric mean leads to more accurate results than the arithmetic mean. Results suggest that it might be possible to reduce errors or expand the application of these assessments by using assessors with less expertise. The wisdom-of-the-crowd effect also can be used to fill in data gaps in life-cycle inventory databases. However, further research is required in this area to explore the practical uses of this phenomenon. The proposed method can be applied to any entity to examine possible improvements in any area of environmental/human health research.